Mitochondrial NAD kinase Pos5 is required for CoQ biosynthesis in yeasts - Shogo Nishihara; Ikuhisa Nishida; Yasuhiro Matsuo; Tomohiro Kaino; Makoto Kawamukai (PLoS ONE, 2026)
Coenzyme Q (CoQ) is an essential component of the electron transport chain, and ten genes involved in CoQ biosynthesis have been identified in Schizosaccharomyces pombe . To gain further insight into CoQ biosynthesis, we screened the Bioneer gene-deletion library and found that the Δpos5 strain produced only 0.2-fold of the wild-type CoQ 10 level. Pos5 shares homology with Saccharomyces cerevisiae Pos5 (ScPos5), a mitochondrial NADH (or NAD + ) kinase that generates NADPH (or NADP + ). Heterologous expression of ScPOS5 in the S. pombe Δ pos5 strain recovered CoQ content to 0.9-fold of the wild-type level, indicating functional conservation of Pos5 between the two yeasts. Consistently, CoQ 6 level in ΔScpos5 was decreased to 0.2-fold of that in the wild-type strain. The Δpos5 strain exhibited several phenotypes characteristic of CoQ-deficient S. pombe , including inability to grow on non-fermentable carbon sources, hypersensitivity to oxidative stress, and high sulfide production. Among CoQ biosynthetic enzymes, Coq6 monooxygenase is thought to utilize NADPH. Supplementation with VA or PHB partially restored CoQ production in the Δpos5 strain, while overexpression of coq6 had negligible effect. These findings suggest that Pos5 is required for the earlier step of CoQ biosynthesis.